Qualidade do leite cru refrigerado obtido em unidades produtoras no sudoeste do Paraná - Belli, Claudinei Zucco Pitro (2015)
The quality of milk is one of the most widely discussed topics in the national dairy production scenario. In this sense, the objective of this study was to evaluate the quality of refrigerated raw milk obtained from mills in partnership with a capture unit, in the Paraná Southwest region. Data collection was carried out of the properties with the aid of a semi-structured questionnaire. They were considered twelve parameters inherent in dairy farming and that can influence the quality of the raw material, as follows: level of production, production systems, milking, cooling, hand labor, technical assistance, assistance often cleaning the cooler, the milking teat disinfection ceilings and structure of the milking environment. Milk samples were analyzed for its composition: fat, protein, lactose, Total Dry Extract (EST), Somatic Cell Count (SCC) and Count Standard on plates (CSP)). The variables were subjected to analysis of variance and is used to compare means the Tukey test at 5% error probability. The protein and SCC were not influenced by any of the tested factors. The fat content is one of the components more likely milk the present variation, which was influenced by the level of production, type of labor, frequency of service, cooler cleaning and type of structure available milking environment on the property. The CSP was influenced by all parameters, except througt the technical assistance, as the same may be directed to other stages of the production process. Treatments that showed higher values for fat and CSP are associated to properties with technological level and lower production. The percentage of establishments that meet the requirements of Instruction 62 (IN 62) for Dry Extract Degreased (DED) is greater than 70% for all tested factors and less than 60% for SCC and CSP in most of the factors studied. The results for fat, protein and lactose are compatible with the minimum requirements set out in IN 62.